Building Religious Moderation through Strengthening the Quality of Human Resources in Madrasah - Emroni, Emroni; Amri, Abduh; Jannah, Raihanatul; Dahlan, Bayani; Fathullah, Amal (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2023)
This study aims to analyze the strengthening of the quality of human resources to build religious moderation in the Madrasah Ibtidaiyah Sullamut Taufiq, Banjarmasin and the Madrasah Ibtidaiyah Nurul Islam, Banjarmasin. This research used a qualitative case study, where data were obtained from interviews, observation and documentation. Data analysis was carried out through data collection, data reduction, data presentation, and concluding. The results of the study show that strengthening the quality of human resources to build religious moderation is carried out through strengthening national commitment through flag ceremonies and learning activities, accommodating to local culture shown in habituation activities and acculturation of madrasa activities, curricular learning, habituation activities, the commemoration of Islamic holidays. This research has implications for the importance of human resources in the success of religious moderation activities in schools so that the spirit of nationalism, patriotism and inclusivism is optimally awakened.